2015
DOI: 10.4236/abb.2015.64032
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Specific Pathogens, Presence of Antibiotics, Aflatoxins, Pesticide Residues and Industrial Contaminants in Supply Chain of Milk in Selected Coastal Districts of Andhra Pradesh

Abstract: A research study was undertaken to carry out isolation and identification of specific pathogens, presence of antibiotics, aflatoxins, pesticide residues and industrial contaminants in supply chain of milk in selected coastal districts of Andhra Pradesh. The milk is a whole food; it is categorized under perishable foods as it is biologically nutrient liquid that supports the growth of wide variety of microorganisms and is susceptible to spoilage. The quality of milk can be affected by the presence of additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Another review by Krishnamoorthy et al [45] reported prevalence estimates of 41% (n = 25, 455; subclinical mastitis) and 27% (n = 6978; clinical mastitis). Farmers will want to initiate mastitis therapy early enough to minimize losses [46] and this may include using broad-spectrum antibiotics [23,47,48]. Medication is mostly delivered into the cow's udder [13] (although injections may be applied in a few of the Table 1 Practices related to antibiotic use in animal health, and their implications in antimicrobial resistance Animal health practices Implications Farm practices (with potential to cause AMR) Chauhan et al [23]; Kumar and Gupta [24] Selling of milk from cows given antibiotics In cases where withdrawal periods have not been observed and residue levels are beyond the recommended levels, consumers can be exposed to low antibiotic doses, which can result to resistant bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another review by Krishnamoorthy et al [45] reported prevalence estimates of 41% (n = 25, 455; subclinical mastitis) and 27% (n = 6978; clinical mastitis). Farmers will want to initiate mastitis therapy early enough to minimize losses [46] and this may include using broad-spectrum antibiotics [23,47,48]. Medication is mostly delivered into the cow's udder [13] (although injections may be applied in a few of the Table 1 Practices related to antibiotic use in animal health, and their implications in antimicrobial resistance Animal health practices Implications Farm practices (with potential to cause AMR) Chauhan et al [23]; Kumar and Gupta [24] Selling of milk from cows given antibiotics In cases where withdrawal periods have not been observed and residue levels are beyond the recommended levels, consumers can be exposed to low antibiotic doses, which can result to resistant bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Another review by Krishnamoorthy et al [ 45 ] reported prevalence estimates of 41% ( n = 25,455; subclinical mastitis) and 27% ( n = 6978; clinical mastitis). Farmers will want to initiate mastitis therapy early enough to minimize losses [ 46 ] and this may include using broad-spectrum antibiotics [ 23 , 47 , 48 ]. Medication is mostly delivered into the cow’s udder [ 13 ] (although injections may be applied in a few of the cases).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, this includes strategies, policies, and legislation to protect food from microbial, chemical, physical, and allergenic contamination during food production, distribution, and consumption [1]. Globally, food pollutants such as heavy metals, mycotoxins, molds, antibiotics, and pesticide residues are becoming increasingly prevalent [2]. Te burden of foodborne diseases remains signifcant with an estimate 600 million illnesses and 420,000 deaths annually [3].…”
Section: Introductionmentioning
confidence: 99%
“…The information on the occurrence of antibiotic drug residues in India is available only in the form of very limited academic research papers. Few such studies have demonstrated the presence of tetracycline residues in milk (Das et al, 2014;Gaurav et al, 2014;Kalla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%